Comparativo da ação do peróxido de hidrogênio 35% e peróxido de carbamida 37% sobre alteração de cor e sensibilidade no clareamento dentário de consultório: um relato de caso - Soares, Gabriella Peixoto de Araújo (2023)
Introduction: Tooth sensitivity is the most common adverse effect related to teeth whitening. In the in-office technique, 37% carbamide peroxide emerged as a possibility to lighten and not cause sensitivity. Objective: The objective of this study was to present a case report that evaluated the efficacy (color change) and the presence or absence of tooth sensitivity when using a product based on 35% hydrogen peroxide (HP) and another based on 37% carbamide peroxide (CP) in the in-office tooth whitening technique. Materials and Methods: Patient E.D., 25 years old, male, submitted to a split-mouth study, where 35% hydrogen peroxide (Whiteness HP - FGM) was applied to the left hemiarch and 37% carbamide peroxide was applied to the right hemiarch (Power Bleaching Office - BM4). There were 3 whitening sessions, CP with a single application of 45 minutes, and PH with 3 applications of 15 minutes, on their respective application side and a seven-day interval between each session. Sensitivity values were analyzed before and after each session using the visual analogue pain scale, and color change was assessed using the Vita Scale, analyzing upper incisors (I) and canines (C) before each session. Results: The patient reported a score of zero (no pain) on the PC side and a score of 4 (moderate pain) for PH. In the region where CP was applied, there was no change in the color of the incisor, remaining at A2, and in the canine it changed from A3.5 to A3, while in the region where the PH was applied, the incisor changed from A2 to A1, and the canine from A3.5 to A2. Teeth whitening with HP showed better whitening efficacy and PC showed no sensitivity during the whitening procedure. Conclusion: Further clinical trial studies with PC are suggested, so that its advantages in terms of sensitivity can be combined with the possibility of delivering better and faster whitening effectiveness.